2013
DOI: 10.5860/rusq.52n4.320
|View full text |Cite
|
Sign up to set email alerts
|

Shall We Get Rid of the Reference Desk?

Abstract: have all advocated for the elimination of the reference desk. 4 Steven Bell has been an active voice in calling for eliminating the reference desk. He reiterated the main problems of the reference desk and said that the reference desk is only a symbol of reference service, not the service itself. He then concluded it is time to eliminate the reference desk and adopt new models. 5What are the problems with traditional reference service? Karen Summerhill pointed out that reference librarians have an inefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 8 publications
1
22
0
1
Order By: Relevance
“…In more recent times, library literature indicates that the trend in academic libraries throughout the United States is to move away from the reference desk to an appointment or consultation-based approach (Meldrem, Mardis, & Johnson, 2005;Tyckoson, 2001) or even roving reference where the librarian meets the patron where they may be studying. However, in a 2011 survey of academic libraries of similar Carnegie Classification, 66.7% reported that they still use the traditional reference desk model to deliver service (Miles, 2013). Based on Regis University Library's previous LibQual+® surveys and personal experience, the Reference Services Department members agreed that the ready accessibility and visibility of the reference librarians is a vital part of their service and marketing efforts.…”
Section: Introductionmentioning
confidence: 97%
“…In more recent times, library literature indicates that the trend in academic libraries throughout the United States is to move away from the reference desk to an appointment or consultation-based approach (Meldrem, Mardis, & Johnson, 2005;Tyckoson, 2001) or even roving reference where the librarian meets the patron where they may be studying. However, in a 2011 survey of academic libraries of similar Carnegie Classification, 66.7% reported that they still use the traditional reference desk model to deliver service (Miles, 2013). Based on Regis University Library's previous LibQual+® surveys and personal experience, the Reference Services Department members agreed that the ready accessibility and visibility of the reference librarians is a vital part of their service and marketing efforts.…”
Section: Introductionmentioning
confidence: 97%
“…Lewis (1995) believed a new paradigm for the mechanics of providing information was needed for libraries to be successful in the forthcoming move to electronic formats for information. From the more-recent literature, the authors found the point-counterpoint exchange between Watstein and Bell (2008) and the thorough summary by Miles (2013) to present balanced accounts Downloaded by [New York University] at 00:28 25 June 2016 of the pros and cons of eliminating desk-based reference services. Their findings made the Executive Team realize that there is no single, correct way to construct a library's desk and reference services.…”
Section: Literature and Statistics Reviewmentioning
confidence: 99%
“…While implementing a Roaming Librarian service outside of the library building is rare (Miles, 2013), literature on the concept does identify some key considerations. Penner (2011) suggests that the key to "any Roving Librarian project should be very simple: be approachable" (p. 29).…”
Section: Literature Reviewmentioning
confidence: 99%